2022
DOI: 10.3390/ijerph19148714
|View full text |Cite
|
Sign up to set email alerts
|

The Role of COVID-19 Vaccine Perception, Hope, and Fear on the Travel Bubble Program

Abstract: The travel bubble program presented an appealing strategy for reopening international travel safely. However, a full vaccination regime is the foremost prerequisite of the program. Therefore, vaccination and the travel bubble are inextricably linked. This study investigated the roles of perceived vaccine efficacy, attitude towards the COVID-19 vaccine, and attitude toward the travel bubble on travel bubble intention. More importantly, the study also examined the mediating role of hope and fear among unvaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
(135 reference statements)
1
5
0
Order By: Relevance
“…Importantly, the results suggested that the strong intention toward booster vaccination in the study sample was the result of individuals' beliefs and moral obligations towards themselves and others. Eventually, the strong intention toward booster vaccination led to a strong intention to travel internationally, which was consistent with previous studies about the correlation between vaccination and international travel [61,67]. The study's findings, however, showed that there is no connection between the desire for immunization and domestic travel.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Importantly, the results suggested that the strong intention toward booster vaccination in the study sample was the result of individuals' beliefs and moral obligations towards themselves and others. Eventually, the strong intention toward booster vaccination led to a strong intention to travel internationally, which was consistent with previous studies about the correlation between vaccination and international travel [61,67]. The study's findings, however, showed that there is no connection between the desire for immunization and domestic travel.…”
Section: Discussionsupporting
confidence: 90%
“…The intention has been defined as a person's proclivity to engage in a specific behavior [60]. Travel intention is defined as the probability and engagement towards the notion of traveling, and it is influenced by a variety of circumstances [61]. The cognitive elements that influenced people's intention to receive booster COVID-19 vaccine for international and democratic travel are the topic of this study.…”
Section: Booster Vaccine Intention and Domestic/international Travel ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a prerequisite for the craftswomen to reactivate their businesses was to have all the doses of the COVID-19 vaccine. According to [33], the attitude and efficacy of COVID-19 vaccination increased the level of hope and showed a strong ability to support tourism revival [34]. It is concluded that vaccination against COVID-19 increases the likelihood of travel; therefore, vaccination boosts tourism participation and, thus, the recovery of the tourism industry.…”
Section: Discussionmentioning
confidence: 99%